(untitled) (Brazilian Journal of Radiation Sciences, 2017)
This work shows the peak voltage measurements for several beam filtrations used in diagnostic radiology, using two types of non-invasive detectors; a voltage meter and a high-resolution spectrometer. The technique chosen for the voltage peak measurements with the spectrometer was the endpoint. The results were compared to the measured ones and showed good similarity to the nominal values. However the voltage meter detector used in this work presented errors for heavier filtrations.